Identification of the mechanisms causing reversion to virulence in an attenuated SARS-CoV for the design of a genetically stable vaccine - Jimenez-Guardeño, Jose Manuel; Regla-Nava, Jose Angel; Nieto-Torres, Jose Luis; DeDiego, Marta L.; Castaño-Rodriguez, Carlos; Fernandez-Delgado, Raul; Perlman, Stanley; Enjuanes, Luis (Public Library of Science, 2015)
A SARS-CoV lacking the full-length E gene (SARS-CoV-∆E) was attenuated and an effective vaccine. Here, we show that this mutant virus regained fitness after serial passages in cell culture or in vivo, resulting in the partial duplication of the membrane gene or in the insertion of a new sequence in gene 8a, respectively. The chimeric proteins generated in cell culture increased virus fitness in vitro but remained attenuated in mice. In contrast, during SARS-CoV-∆E passage in mice, the virus incorporated a mutated variant of 8a protein, resulting in reversion to a virulent phenotype. When the full-length E protein was deleted or its PDZ-binding motif (PBM) was mutated, the revertant viruses either incorporated a novel chimeric protein with a PBM or restored the sequence of the PBM on the E protein, respectively. Similarly, after passage in mice, SARS-CoV-∆E protein 8a mutated, to now encode a PBM, and also regained virulence. These data indicated that the virus requires a PBM on a transmembrane protein to compensate for removal of this motif from the E protein. To increase the genetic stability of the vaccine candidate, we introduced small attenuating deletions in E gene that did not affect the endogenous PBM, preventing the incorporation of novel chimeric proteins in the virus genome. In addition, to increase vaccine biosafety, we introduced additional attenuating mutations into the nsp1 protein. Deletions in the carboxy-terminal region of nsp1 protein led to higher host interferon responses and virus attenuation. Recombinant viruses including attenuating mutations in E and nsp1 genes maintained their attenuation after passage in vitro and in vivo. Further, these viruses fully protected mice against challenge with the lethal parental virus, and are therefore safe and stable vaccine candidates for protection against SARS-CoV.
Keywords: Virus; Virología; COVID-19; Coronavirus; Virus; Virology; SARS-CoV; Coronavirus